2021
DOI: 10.1186/s12936-021-03885-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cattle on the abundance of indoor and outdoor resting malaria vectors in southern Malawi

Abstract: Background Understanding the blood feeding preferences and resting habits of malaria vectors is important for assessing and designing effective malaria vector control tools. The presence of livestock, such as cattle, which are used as blood meal hosts by some malaria vectors, may impact malaria parasite transmission dynamics. The presence of livestock may provide sufficient blood meals for the vectors, thereby reducing the frequency of vectors biting humans. Alternatively, the presence of cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…The result of this study showed sleeping in the same house with cattle was the main determinant factor for malaria (p = 0.031). This finding is in agreement with other similar study conducted in Malawi [ 78 ]. The availability of alternative hosts such as livestock near or inside residential houses could make suitable mosquito breeding sites as well as could attract more mosquitoes towards the house.…”
Section: Discussionsupporting
confidence: 94%
“…The result of this study showed sleeping in the same house with cattle was the main determinant factor for malaria (p = 0.031). This finding is in agreement with other similar study conducted in Malawi [ 78 ]. The availability of alternative hosts such as livestock near or inside residential houses could make suitable mosquito breeding sites as well as could attract more mosquitoes towards the house.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to the north, several biting peaks were recorded at the southern sites, where two rainy seasons are observed yearly, except during the short dry season from November to January. Interestingly, all the vectors showed outdoor biting patterns throughout both years and at all sites, even though several animal shelters were found in the northern sites, which could drive the mosquitoes outdoors [32,33]. Furthermore, the endophagic rates recorded in Gounougou and Simatou were lower than those of the southern sites because of the presence of great number of cattle farms.…”
Section: Discussionmentioning
confidence: 96%
“…In situations in which livestock are kept close to humans, the presence of animals may increase the risk of human-biting simply through the cattle attracting mosquitoes to the general proximity [ 85 87 ]. In contrast, the presence of livestock at households has also been shown to reduce human-feeding rates [ 77 , 88 , 89 ]. These contradictory observations may be attributed to variations in host preference and abundance of the dominant vector species, as well as in the distance of livestock from households [ 90 ].…”
Section: Discussionmentioning
confidence: 99%